Políticas públicas educacionais e letramento digital: subsídios para a conscientização sobre fake news nas escolas - Gonçalves, Tais Fabiola (Universidade do Vale do Rio dos Sinos, 2025)
The high vulnerability of children and adolescents to the online environment and the unpreparedness of a significant portion of educators to address this topic in the classroom constitute a practical and urgent challenge for Brazilian education. This research in the field of educational management addresses a gap between the formulation of public policy and the practical need for awareness regarding fake news in the school environment. The research problem sought to answer how educational public policies support digital literacy for fake news awareness within the school context, as the effectiveness of these policies in the "school floor" reality is a challenge seldom explored in an integrated manner in the literature. A qualitative, descriptive study was conducted based on a bibliographic and documentary analysis. The analyzed documents included seven legal instruments, such as legislation, opinions, and resolutions, in addition to official guides and reports from the Brazilian government. Furthermore, nineteen surveys were utilized, including data from the Higher Education Census, Cetic.br (ICT Education Survey), and UNESCO. The results indicated that although Brazil possesses an advanced legal framework, such as the National Policy on Digital Education (PNED), its implementation is hindered by infrastructural barriers and, most notably, by the lack of continuous teacher training. Nevertheless, it was possible to identify means of bridging the gap between policy and local reality, such as investing in articulation between government spheres and creating municipal-level regulations. This research contributed to the academic and scientific field by deepening the concept of digital awareness in light of Paulo Freire's theoretical framework; in the field of applied research, by providing a real intervention material—a Recommendation approved by the Municipal Council of Education of São Leopoldo, RS, which serves as a model for other localities; and it also made contributions to the social sphere, by assisting schools in the quest to form critical citizens who are better prepared for the challenges of the digital age.
Keywords: Políticas públicas educacionais; Letramento digital; Fake news; Conscientização digital; Gestão educacional; Educational public policies; Digital literacy; Digital awareness; Educational management; ACCNPQ::Ciências Humanas::Educação